Molecular epidemiology of gonorrhoea in Wales (UK). Issue 3 (5th December 2012) - Cole, Michelle J; Thomas, Daniel Rh; Chisholm, Stephanie A; Abdullah, Adel N; Birley, Humphrey; Hosein, Ian; Kubiak, Elizabeth; White, Diana; Martin, Iona; Ison, Catherine A
Abstract : Objectives: After a trend of increasing incidence of gonorrhoea in the 1990s, by 2004 the incidence was declining in England, but continuing to increase in Wales. This prompted an investigation of the epidemiology of gonorrhoea in Wales to inform future prevention and control measures. Methods: As an extension to Gonococcal Resistance to Antimicrobials Surveillance Programme, between May 2005 and September 2006, 540 consecutive gonococcal isolates were collected from three microbiology laboratories in South Wales. Isolates were typed using Neisseria gonorrhoeae Multi Antigen Sequence Typing tested for susceptibility to therapeutic agents and demographic and behavioural data were collected retrospectively from patient notes. Results: 163 sequence types (STs) were identified in 475 N gonorrhoeae isolates from 502 patient episodes. The most frequently observed STs (>20 isolates) were: 2, 752, 471, 249 and 8, all of which were susceptible to the antimicrobial agents tested. A significant association between ST and sexual orientation was identified, the most frequently observed STs occurring in young (median age <25 years) heterosexuals. STs 147, 4, 1634 and 64 predominated in men who have sex with men. Conclusions: We confirm the existence of common STs across the UK, as well as identify a number of types that were novel to Wales. Discrete sexual networks were identified, the most localised being in young heterosexuals. Molecular typing provides a method for identifying local clusters of gonorrhoea, and could assist in the implementation and evaluation of targeted interventions.